52.1k views
1 vote
What is the solutions of the following system of equations.

y = -2x + 2

y = x - 1

1 Answer

7 votes

Answer:

x = 1, y = 0

Explanation:

Given the 2 equations

y = - 2x + 2 → (1)

y = x - 1 → (2)

Substitute y = x - 1 into (1)

x - 1 = - 2x + 2 ( add 2x to both sides )

3x - 1 = 2 ( add 1 to both sides )

3x = 3 ( divide both sides by 3 )

x = 1

Substitute x = 1 into either of the 2 equations for corresponding value of y

Substituting into (2)

y = 1 - 1 = 0

Solution is (1, 0 )

User Michael Blood
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.